PENGARUH E-SERVQUAL TERHADAP CUSTOMER SATISFACTION, TRUST, DAN WORD OF MOUTH PESERTA BPJS KETENAGAKERJAAN - AN, I Wayan Mahendra Putra; Wardana, I Made; Sukaatmadja, I Putu Gd (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.11.TAHUN 2016, 2016)
Social security has been accepted as an instrument for the prevention and alleviation of poverty because it can increase the productivity of labor. Submission of the convenience of information and services via the Internet has been adopted to support it. The purpose of this study was to clarify the effect of e-servqual to customer satisfaction, trust, and word of mouth participants BPJS Ketenagakerjaan. The research data were used in the form of figures the growth rate of Internet users, the numbers increase user participation and online services BPJS Ketenagakerjaan, as well as the distribution of the questionnaire to test the variables in the study, using purposive sampling techniques BPJS Ketenagakerjaan to 100 participants who have been using online services. The analytical method used, namely, Structural Equation Model (SEM) with the application of SPSS and AMOS. This study showed that, the whole hypothesis can be accepted that e-servqual contribute positively and significantly to customer satisfaction, trust, and word of mouth. customer satisfaction and significant positive role towards trust, and word of mouth. trust plays a positive and significant impact on word of mouth. The theoretical implication of this study further enrich the theories e-servqual, customer satisfaction, trust, and word of mouth. Managerial implication in this study suggested that the BPJS Ketenagakerjaan consider factors - factors other than the dimensions of responsiveness as socializing on a regular basis for security and ease of use of online services, as well as providing stimulus to participants who are able to invite others to sign up as a participant.
Keywords: E-Servqual, Customer Satisfaction, Trust, and Word of Mouth